Innovation and Development of Language Learning Media Information Technology based Through Wattpad Application - Efendi, Novita; Zaim, M; Thahar, Harris Effendi; Atmarizon, Diki (International Journal of Educational Dynamics, 2023)
Application are software designed to run on electronic devices such as computers, smartphones, tablets or other devices. Apps can serve a variety of purposes, including helping users perform certain tasks, accessing information, interacting with other users, entertaining, or performing other functions desired by the user. The purpose of this research is to see how effectively the use of the Wattpad application can support language learning media in schools. The Wattpad application is a digital platform-based application that allows users to read, send and share stories and works of fiction in text form submitted by other users or authors registered on the Wattpad platform. The research subjects were junior high school level students. The interview method is used as a tool to collect data. The results of the study show that the Wattpad application is a language learning medium that can improve learning outcomes. The rest admitted that they were very interested in learning reading and writing skills through Wattpad. In addition, the Wattpad application also provides a fun learning experience for students.